Creep rupture study of dissimilar welded joints of P92 and 304L steels - Dak, Gaurav; Guguloth, Krishna; Vidyarthy, R. S.; Fydrych, Dariusz; Pandey, Chandan (Welding in the world, 2024)
The present work investigates the high-temperature tensile and creep properties of the dissimilar metal weld joints of 304L austenitic stainless steel (SS) and P92 creep strength-enhanced ferritic-martensitic (CSEF/M) steel under different testing condition. Thermanit MTS 616 filler rod (P92 filler) and the multi-pass tungsten inert gas (TIG) welding process were used to create the dissimilar weld connection. The ultimate tensile strength (UTS) was evaluated in the temperature range of 450–850 °C. Creep testing was conducted at a temperature of 650 °C while applying stress levels of 130 MPa, 150 MPa, 180 MPa, and 200 MPa. The shortest creep life (2.53 h) was recorded for the specimen tested at 650 °C and subjected to 200 MPa, whereas the longest creep life (~ 242 h) was observed for the specimen tested at 650 °C with a stress of 130 MPa. The linear regression model was developed using an applied stress (σ) v/s rupture time (t R ) plot at 650 °C. The applied stress and rupture time followed the logarithmic equation: log(t R ) = 22.57566 + (-9.55294) log (σ). The detailed microstructural characterization and micro-hardness distribution across the fractured specimens was carried out. The findings demonstrated that the service life span of this weld joint at high temperature and stress conditions is influenced by the undesired microstructural changes at elevated temperature, such as coarsening of the precipitates, development of the Laves phase, softening of the matrix, and strain-ageing phenomenon.